Gates of Consciousness: Buddhist Phenomenology of Cognition in the Abhidhamma - Federico Divino (Philosophies, 2025)
This article aims to provide a comparative analysis between Husserl’s phenomenology and the Pāli Abhidhamma. To conduct this analysis, I will mainly draw on some books of the Abhidhamma and three works by Husserl. What emerges from this study are interesting convergences between the two systems of thought, which allow us to consider, in some respects, a true Buddhist phenomenology codified in the Abhidhamma. While not perfectly coinciding with Husserl’s phenomenology, it is similar enough to allow for a comparative study and perhaps even more. The intent is also to propose the possibilities of a true Buddhist phenomenology based on its methodology, and thus, not to see differences with Husserl’s approach as a limitation, but as something that can enrich the phenomenological methodology itself.